On the prospects of land consolidation in Ukraine - Koshel, A.; Kolhanova, I.; Kempa, O. (Land Management, Cadastre and Land Monitoring, 2025)
Abstracts. The article deals with the topical issue of land consolidation in Ukraine as a tool for improving the efficiency of land use and ensuring sustainable development of rural areas. The author analyses the current state of land resources, problems of their fragmentation and irrational use that have arisen as a result of land relations reform.Particular attention is paid to the regulatory and legal aspects of land consolidation, identification of the main obstacles to its implementation and development prospects in the context of decentralisation. The main stages and procedures of consolidation, its impact on the economic, environmental and social aspects of the functioning of territories are highlighted.  The article offers recommendations for improving the organisational and legal support of the consolidation process, introducing modern land management tools and involving communities in planning and implementing land consolidation measures.The results of the study can be used to prepare land management projects, as well as in shaping state policy in the field of land management.  Keywords: land consolidation, land resources, land management, efficient land use, protection of agricultural land, land management.
Keywords: land consolidation; land resources; land management; efficient land use; protection of agricultural land